Essays on Executive Stock Options. - Felipe Rodrigues Cruz (2022)
Based on several theoretical studies on how to build optimal management compensation contracts that reduce or eliminate manipulation, we theoretically and empirically investigate how features of an Executive Stock Option Plan (ESOP) affect managers’ behavior. Our thesis is that ESOP features can reduce managers’ manipulative incentives. We test this hypothesis through three different studies. In our first study, we analyze theoretical arguments on ideal features of an ESOP and investigate whether companies traded in the Brazilian Exchange conform to these. We specifically focus on contract time horizon, strike price setting and re-setting mechanisms, dividend protection and corporate governance, as the literature suggests that these features affect manipulation incentives. Brazilian companies conform to some of the ideal features, such as high quality monitoring devices (corporate governance), but could enhance their strike-price (re)setting mechanisms and adopt longer incentive horizons, as these are better suited to deal with manipulative behavior. By not including price re-setting provisions, these companies were unable to react the effects of the pandemic on stock market prices. Regarding the association between contract features and manipulation, in our second study, we analyze how ESOP features affect Earnings Quality (EQ) measures. We analyze how management stock options affect Earnings Persistence, Discretionary Accruals, Target Earnings Measures and Earnings Smoothness. We find that firms that adopt compensation contracts that include long-term incentives (incentives that last longer than five years) have higher EQ as measured by persistence, smoothness and discretionary accruals. However, managers with longer contracts might artificially enhance EQ measures, as they are more likely to miss specific target earning measures if a large sum of their options vests in the following year. We also find that large option grants in the following year exacerbate manipulations in the current year, leading manager to utilize negative manipulation of discretionary accruals in order to miss target-earning measures, reducing granted options’ strike prices. Nevertheless, better monitoring devices (higher board independence and not having a CEO that is also the Board Chairman) within optioned-companies enhances EQ. At last, in our third and last study we focus on how ESOP affect dividend payments and share repurchases. We find that non-dividend-protected stock option plans (NDPESOP) lead companies to pay smaller dividends relative to their market value, as dividends negatively affect managers’ stock option gains within these plans context. By guaranteeing that managers will receive dividends paid during the vesting period, dividend-protected ESOP (DPESOP) nullify the negative effect of NDPESOP on dividends. We also find that both DPESOP and NDPESOP positively affect share repurchases, which contradicts previous literature that has stated that the lack of dividend protection leads managers to substitute dividends for repurchases in order to maintain payout levels unaltered. At last, we find new evidence on why some companies adopt dividend protection and others do not. By including a dividend protection in ESOP, managers no longer have incentives to reduce dividend payments. Accordingly, we find that monitoring incentives (corporate governance and foreign ownership) explain dividend protection, which suggests that dividends play a monitoring role in Brazilian companies.